Mineralogical examination of biomass ashes: A preliminary study for potassium enrichment and phosphoric acid (H3PO4) production - Duran Serdar Karahan; Gülsüm Turgut; Arzu Yavuz; Ufuk Kibar; Mustafa Albayrak; Mehmet Çöteli (Bulletin of the Mineral Research and Exploration)
In this study, biomass fly ash was investigated and determined by XRD to be predominantly langbeinite, aphthitalite, sylvine, apatite and hydroxyapatite. An alkaline leaching study was carried out on the material in a glass reactor at l/s ratio 4 temperature 600C at pH 12.85 and after drying was analyzed by ICP. The crystal structure composition of K2SO4 72.28% and potassium content of 33.47%(w/w) was recovered. The elemental transformations in this leaching process were: K 74.16%, Mg 0.55% was found to be 0.8%. It was found that a minimum of 4.84 g H2SO4 per 100 g fly ash was required to precipitate the Ca(OH)2 migrated into the liquid solution and the overall leaching efficiency was found to be 29.85%. In the alkaline leaching process, potassium was found to be easily recovered from each biomass ash. By adding 40 g H2SO4/100 g biomass waste remaining after leaching, a phosphorus recovery of 74.9% was observed. In this preliminary study, unsatisfactory results were obtained in obtaining the industry standard H3PO4. The reason for this is that the Al, Mg and K in the fly ash are subject to selective dissolution as a result of working at high pH in the alkaline leaching process.